Issues Occurrence of Career Success Among Female Engineers - Amalia, Madihie; Rose Amira, Siman (UNIMAS Publisher, 2016)
This research aims to identify the issues among female engineers in the perspective of their career success. The issues that were identified are work-life balance, gender stereotyping and slow progression on the career success. The research design is a qualitative approach by in-depth interview. The research design which consisted of ten items aimed to explore female engineers’ satisfaction of working in the construc-tion industry, unequal employment in the workplace, persistent problems in managing work-life balance, the role of gender in developing career success and also factors that positively and negatively affect the retention of female engineers in the construc-tion industry. Five participants were recruited from various construction companies in Malaysia. Four of them were interviewed via phone calls and one via electronic mail. The findings from this research show that work-life balance issue is the main issue. Other issues include gender stereotype, nature of work and the competition among male and female engineers. From these findings, one recommendation is that the top management of an organization can provide full support to the employees so that they can be more productive in the workplace and are able to balance their work and non-work responsibilities.